Genomics insight on passion fruit viral disease complexity - Munguti, F.; Nyaboga, E.N.; Holton, Timothy; Kreuze, J.F.; Maina, S. (American Society for Microbiology, 2025)
Passion fruit viral diseases pose a significant threat to Kenya’s passion fruit industry. To unravel the complexity of these diseases, comprehensive virus surveys were conducted across major passion fruit-growing counties. Passion fruit woodiness disease symptoms, like fruit hardening, chlorotic mottling, and leaf distortion, were prevalent. The study unveiled the first 23 complete genomes of Ugandan passiflora virus (UPV) and two East Asian passiflora distortion virus (EAPDV) in Kenya. UPV showed 99% nucleotide (nt) match to a UPV genome from Uganda and 66% nt identity match to EAPDV. In addition, UPV variants and two partial passion fruit green spot virus sequences and partial (passiflora emaravirus) segment RNA1-5 (novel allexivirus and an emaravirus, respectively) were detected. Phylogenetic analysis revealed distinct lineages (I–III), indicating potential multiple introductions into Kenya. Recombination analysis detected no significant breakpoints. However, the study proposed the renaming of EAPDV to passiflora distortion virus (PDV) and UPV to passiflora virus (PV) for neutral nomenclature, without geographical association. Additionally, the study highlighted the role of coinfections in symptom expression, suggesting a potential synergistic relationship between PV, PDV, and other viruses. The results recommend stringent management strategies and enhanced surveillance to mitigate the economic impact of these viruses on the Kenyan passion fruit industry. The findings from this study underscore the need to strengthen nursery certification programs and pest diagnostic protocols in Kenya. Additionally, enhanced pest surveillance and import regulations are critical to preventing the introduction and spread of emerging plant viral diseases, thereby safeguarding the country’s horticultural productivity and biosecurity. To our knowledge, this is the first comprehensive study of viral diseases of passion fruit in Kenya.